Predictive Biomarkers of Acute Kidney Injury in COVID-19: Distinct Inflammatory Pathways in Patients with and Without Pre-Existing Chronic Kidney Disease - Caterina Carollo; Alida Benfante; Alessandra Sorce; Katia Montalbano; Emanuele Cirafici; Leonardo Calandra; Giulio Geraci; Giuseppe Mulè; Nicola Scichilone (Life)
Background: Acute kidney injury (AKI) has emerged as a significant complication in patients with coronavirus disease 2019 (COVID-19). The pathophysiology of COVID-19-associated AKI is multifactorial, involving both direct viral effects on renal cells and indirect mechanisms such as systemic inflammation and cytokine storms. This highlights the critical need for early detection and effective management strategies to mitigate kidney injury and improve patient outcomes. The aim of our study is to assess the potential predictive role of inflammatory biomarkers in determining the risk of developing COVID-19-associated AKI in patients with and without pre-existing CKD. Methods: This study included 84 patients stratified by pre-existing chronic kidney disease (CKD) status. Demographic, clinical, and laboratory data were collected, including vital signs, hematological profiles, renal function markers, inflammatory biomarkers, coagulation parameters, and treatments. Outcomes such as acute kidney injury (AKI) and in-hospital mortality were documented. Results: In patients with pre-existing CKD, IL-6 and NLR demonstrated high predictive accuracy for AKI onset. In patients without pre-existing CKD, white blood cell (WBC) count emerged as a significant predictor of AKI onset. Conclusions: The differential roles of IL-6, NLR, and WBC in predicting AKI onset highlight distinct physiopathological pathways influenced by COVID-19. In CKD+ patients, chronic inflammation and immune dysregulation are key drivers of AKI, with IL-6 and NLR serving as robust markers of this inflammatory state. In contrast, in CKD− patients, AKI may be more influenced by acute inflammatory responses and infectious factors, as reflected by WBC count.